MANAJEMEN BUDAYA KESELAMATAN DALAM MENINGKATKAN MUTU PELAYANAN PASIEN - Abdul Ghofar; Indah Lestari; Faisal Ibnu (Universitas Pesantren Tinggi Darul Ulum, 2022)
Patient Safety Culture (PSC) is first step in developing patient safety. Patient safety is core of the quality of health services in hospitals. Hospitals are responsible for improving the quality of health services in managing patient safety. This study used literature review by an electronic search for articles PubMed, Science Direct, Google Schoolar and Pro Quest with a manual bibliographic includes articles and key journals. We studies in American, European, Asian and African focused on management of PSC and patient safety. We independently verifies the study meets inclusion criteria and critically assesses quality of study. Researchers identified 23 studies met the inclusion criteria. The review identified main dimensions in PSC management include developing teamwork and organization, supervisor expectations and learning behaviors for hospital staff. Fault reporting and safety awareness, gender and demographics, work experience, and staffing are additional dimensions. Other management by conducting a survey regularly every two or three years and used an internationally standardized instrument HSOPSC from AHRQ. The managing quality patient safety in hospitals, several steps are governance and regulation of patient safety, education and training, patient involvement, measurement and monitoring of patient safety, the use of information technology in supporting services that prioritize quality patient safety. Main dimensions in developing PSC are teamwork and organization, supervisor expectations and learning behavior for hospital staff. Factors affect patient safety management are organizational systems, education and training, involving patients and information technology. Keywords: Management, Patient safety culture, Patient safety, Service quality